ANALISIS KEPATUHAN MAQASHID SYARIAH DALAM TRANSAKSI DIGITAL PERBANKAN SYARIAH : STUDI LAYANAN BSI MOBILE - Abdur Rokhim; Supardi; Laila Afni Rambe (KASBANA, 2026)
Abstract The development of digital services in Islamic banking has undergone significant transformation, one of which is through the BSI Mobile application presented by Bank Syariah Indonesia (BSI). This study aims to analyze the alignment of the fund transfer service on the BSI Mobile application with the principles of Maqashid Sharia, which include the protection of religion (hifz ad-din), life (hifz an-nafs), intellect (hifz al-'aql), descendants (hifz an-nasl), and property (hifz al-mal). The research method used was descriptive qualitative, with a library research approach, interviews, and observation. The results indicate that the fund transfer service through BSI Mobile complies with the principles of Maqashid Sharia and aligns with the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), particularly in terms of transaction security, ease of access, and cost transparency. However, several areas still need improvement to ensure a more comprehensive implementation of Sharia principles. Keywords: Digital Services, Bank Syariah Indonesia, Fund Transfer, BSI Mobile, Maqashid Syariah.